Electronic structure of the Si(111)3×3R30∘−B surface from theory and photoemission spectroscopy - Aldahhak, Hazem; Hogan, Conor; Lindner, Susi; Appelfeller, Stephan; Eisele, Holger; Schmidt, Wolf Gero; Dähne, Mario; Gerstmann, Uwe; Franz, Martin (Physical Review B)

Dark-state and loss-induced phenomena in the quantum-optical regime of Λ-type three-level systems - Rose, Hendrik; Popolitova, D. V.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Approximate nonlinear wave solutions of the coupled two-component Gross–Pitaevskii equations with spin–orbit interaction - Belobo, Didier Belobo; Meier, Torsten (New Journal of Physics)

Impact of screening and relaxation on weakly coupled two-dimensional heterostructures - Nguyen, T. T. Nhung; Sollfrank, T.; Tegenkamp, C.; Rauls, E.; Gerstmann, Uwe (Physical Review B)

Friction-Induced Recycling Process for User-Specific Semi-Finished Product Production - Borgert, Thomas; Homberg, Werner (Metals)
Modern forming processes often allow today the efficient production of complex parts. In order to increase the sustainability of forming processes it would be favorable if the forming of workpieces becomes possible using production waste. At the Chair of Forming and Machining Technology of the Paderborn University (LUF) research is presently conducted with the overall goal to produce workpieces directly from secondary aluminum (e.g., powder and chips). Therefore, friction-based forming processes like friction spinning (or cognate processes) are used due to their high efficiency. As a pre-step, the production of semi-finished parts was the subject of accorded research work at the LUF. Therefore, a friction-based hot extrusion process was used for the full recycling or rework of aluminum chips into profiles. Investigations of the recycled semi-finished products show that they are comparable to conventionally produced semi-finished products in terms of dimensional stability and shape accuracy. An analysis of the mechanical properties of hardness and tensile strength shows that a final product with good and homogeneously distributed properties can be produced. Furthermore, significant correlations to the friction spinning process could be found that are useful for the above-mentioned direct part production from secondary aluminum.

Influence of Chemical Blowing Agents on the Filling Behavior of Wood-Plastic-Composite Melts - Moritzer, Elmar; Flachmann, Felix (SPE ANTEC 2021: The Annual Technical Conference for Plastic Professionals)

Modelling of a continuous distillation process with finite reflux ratio using the hydrodynamic analogy approach - Bolenz, Lukas; Ehlert, Thomas; Dechert, Christopher; Bertling, René; Kenig, Eugeny (Chemical Engineering Research and Design)

Influence of rivet length on joint formation on self-piercing riveting process considering further process parameters - Kappe, Fabian; Bielak, Christian Roman; Sartisson, Vadim; Bobbert, Mathias; Meschut, Gerson (ESAFORM 2021)
Driven by the CO2-emission law by the European government and the increasing costs for raw materials as well as energy, the automotive industry is increasingly using multi-material constructions. This leads to a continuous increase in the use of mechanical joining techniques and especially the self-piercing riveting is of particular importance. The reason for this is the wide range of joining possibilities as well as the high load-bearing capacities of the joints. To be able to react to changing boundary conditions, like material thickness or strength variation of the sheets, research work is crucial with regard to the increase of versatility. In this paper, a numerical study of the influences on the selfpiercing riveting process is presented. For this purpose, the influence of different process parameters such as rivet length and die depth on various quality-relevant characteristics were investigated. With the help of the design of experiment, significant influences were determined and interactions between the individual parameters are shown.

Numerical and Experimental Fracture Mechanical Investigations of Clinchable Sheet Metals Made of HCT590X - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Key Engineering Materials)
In many areas of product manufacturing constructions consist of individual components and metal sheets that are joined together to form complex structures. A simple and industrial common method for joining dissimilar and coated materials is clinching. During the joining process and due to the service load cracks can occur in the area of the joint, propagate due to cyclic loading and consequently lead to structural failure. For the prevention of these damage cases, first of all knowledge about the fracture mechanical material parameters regarding the original material state of the sheet metals used within the clinching process are essential.Within the scope of this paper experimental and numerical preliminary investigations regarding the fracture mechanical behavior of sheet metals used within the clinching process are presented. Due to the low thickness of 1.5 mm of the material sheets, the development of a new specimen is necessary to determine the crack growth rate curve including the fracture mechanical parameters like the threshold against crack growth ΔK I,th and the fracture toughness K IC of the base material HCT590X. For the experimental determination of the crack growth rate curve the numerical calculation of the geometry factor function as well as the calibration function of this special specimen are essential. After the experimental validation of the numerically determined calibration function, crack growth rate curves are determined for the stress ratios R = 0.1 and R = 0.3 to examine the mean stress sensitivity. In addition, the different rolling directions of 0° and 90° in relation to the initial crack are taken into account in order to investigate the influence of the anisotropy due to rolling.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Holistic investigation chain for the experimental determination of fracture mechanical material parameters with special specimens - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Production Engineering)
Abstract In addition to the classical strength calculation, it is important to design components with regard to fracture mechanics because defects and cracks in a component can drastically influence its strength or fatigue behavior. Cracks can propagate due to operational loads and consequently lead to component failure. The fracture mechanical analysis provides information on stable or unstable crack growth as well as about the direction and the growth rate of a crack. For this purpose, sufficient information has to be available about the crack location, the crack length, the component geometry, the component loading and the fracture mechanical material parameters. The fracture mechanical properties are determined experimentally with standardized specimens as defined by the guidelines of the American Society for Testing and Materials. In practice, however, especially in the context with damage cases or formed material fracture mechanical parameters directly for a component are of interest. However, standard specimens often cannot be extracted at all due to the complexity of the component geometry. Therefore, the development of special specimens is required whereby certain arrangements have to be made in advance. These arrangements are presented in the present paper in order to contribute to a holistic investigation chain for the experimental determination of fracture mechanical material parameters with special specimens.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Modeling of gyroidal mesoporous CMK-8 and CMK-9 carbon nanostructures and their X-Ray diffraction patterns - Schwind, Bertram; Smått, Jan-Henrik; Tiemann, Michael; Weinberger, Christian (Microporous and Mesoporous Materials)
Powder X-ray diffraction (XRD) patterns of ordered mesoporous CMK-8 and CMK-9 carbon materials are simulated by geometric modeling. The materials are amorphous at the atomic length scale but exhibit highly symmetric gyroidal structures at the nanometer scale, corresponding to regular, continuous nanopore systems with cubic symmetry. Their structures lead to characteristic low-angle XRD signatures. We introduce a model based on geometrical considerations to simulate CMK-8 and CMK-9 structures with variable volume fraction of carbon (vs. pore volume, i.e., variable 'pore wall thickness'). In addition, we also simulate carbon materials with variable amounts of guest species (e.g., sulfur) residing in their pores. The corresponding XRD patterns are calculated. The carbon volume fraction turns out to have a significant impact on the relative diffraction peak intensities, especially in case of CMK-9 carbon that features a bimodal porosity. Likewise, the presence of guest species in the pores may also strongly affect the relative peak intensities. Our study suggests that careful evaluation of experimental low-angle XRD patterns of (real) CMK-8 or CMK-9 materials offers an opportunity to obtain detailed information about the nanostructural properties in addition to the mere identification of the pore systems geometry.

Review of infrared spectroscopy techniques for the determination of internal structure in thin SiO2 films - de los Arcos, Teresa; Müller, Hendrik; Wang, Fuzeng; Damerla, Varun Raj; Hoppe, Christian; Weinberger, Christian; Tiemann, Michael; Grundmeier, Guido (Vibrational Spectroscopy)
A comparison of infrared spectroscopic analytical approaches was made in order to assess their applicability for internal structure characterization of SiO2 thin films. Markers for porosity and/or disorder based on the analysis of the asymmetric stretching absorption band of SiO2 between 900−1350 cm−1 were discussed. The shape of this band, which shows a well-defined LO–TO splitting, depends not only on the inherent characteristics of the film under analysis but also on the particular geometry of the IR experiment and the specific surface selection rules of the substrate. Three types of SiO2 thin films with clearly defined porosity ranging from dense films to mesoporous films were investigated by transmission (at different incidence angles), direct specular reflection (at different angles), and diffuse reflection. Two different types of substrate, metallic and semiconducting, were used. The combined effect of substrate and specific technique in the final shape of the band, was discussed, and the efficacy for their applicability to the determination of porosity in thin SiO2 films was critically evaluated.

Selective Modification of Hierarchical Pores and Surfaces in Nanoporous Materials - Tiemann, Michael; Weinberger, Christian (Advanced Materials Interfaces)
Tailor-made ordered mesoporous materials bear great potential in numerous fields of application where large interfaces are required. However, the inherent surfacechemical properties of conventional materials, such as silica, carbon or organosilica, poses some limitations with respect to their application. Surface manipulation by functionalization with chemically more reactive groups is one way to improve materials for their desired purpose. Another approach is the design of high surface-area composite materials. The surface manipulation, either by functionalization or by introducing guest species, can be performed selectively. This means that when several distinct, i.e. , hierarchical, types of surfaces or pore systems exist in a material, each of them may be chosen for manipulation. Several strategies can be identified to achieve this goal. Molecules or molecule assemblies can be utilized to temporarily protect pores or surfaces (soft protection), while manipulation occurs at the accessible sites. This approach is a recurring motive in this review and can also be applied to rigid template matrices (hard protection). Furthermore, the size of functionalization agents (size protection) and their reactivity/diffusion (kinetic protection) into the pores can also be utilized to achieve selectivity. In addition, challenges in the synthesis and characterization of selectively manipulated ordered mesoporous materials are discussed.

Engels@200: Friedrich Engels in the Age of Digital Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

卡尔·马克思与互联网研究 - Fuchs, Christian; Dyer-Witheford, Nick (国际社会科学杂志 (Journal of International Social Sciences) 2021 (9))

Examination of the evolution of iron oxide nanoparticles in flame spray pyrolysis by tailored in situ particle sampling techniques - Tischendorf, R.; Simmler, M.; Weinberger, Christian; Bieber, M.; Reddemann, M.; Fröde, F.; Lindner, J.; Pitsch, H.; Kneer, R.; Tiemann, Michael; Nirschl, H.; Schmid, H.-J. (Journal of Aerosol Science)
In this report, a flame spray pyrolysis setup has been examined with various in situ extraction methods of particle samples along the flame axis. First, two precursor formulations leading to the formation of iron oxide nanoparticles were used in a standardized SpraySyn burner system, and the final particle outcome was characterized by a broad range of established powder characterization techniques (TEM/HRTEM, SAXS, XRD, BET). The characterization of the powder products evidenced that mostly homogeneous gas-to-particle conversion takes place when applying an acidic precursor solution, whereas the absence of the acid leads to a dominant droplet-to-particle pathway. Our study indicates that a droplet-to-particle-pathway could be present even when processing the acidic formulation. However, even if a secondary pathway might take place in this case as well, it is not dominant and nearly negligible. Subsequently, the in situ particle structure evolution was investigated for the dominant gas-to-particle pathway, and particles were extracted along the flame axis for online SMPS and offline TEM/HRTEM analysis. Due to the highly reactive conditions within the flame (high temperatures, turbulent flow field, high particle number concentrations), the extraction of representative samples from spray flames is challenging. In order to handle the reactive conditions, two extraction techniques were tailored in this report. To extract an aerosol sample within the flame for SMPS measurement, a Hole in a Tube probe was adjusted. Thus, the mobility particle diameter as well as the corresponding distribution widths were obtained at different heights above the burner along the flame axis. For TEM/HRTEM image analysis, particle samples were collected thermophoretically by means of a tailored shutter system. Since all sampling grids were protected until reaching the flame axis and due to the low sampling time, momentary captures of local particle structures could be extracted precisely. The particle morphologies have clearly shown an evolution from spherical and paired particles in the flame center to fractal and compact agglomerates at later synthesis stages.

TiO2 nanoparticle coatings on glass surfaces for the selective trapping of leukemia cells from peripheral blood - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Weinberger, Christian; Schwiderek, Sabrina; Knust, Steffen; Tiemann, Michael; Grundmeier, Guido; Keller, Adrian; Camargo Amado, Ruben Jesus (Journal of Biomedical Materials Research Part B: Applied Biomaterials)
Photodynamic therapy (PDT) using TiO2 nanoparticles has become an important alternative treatment for different types of cancer due to their high photocatalytic activity and high absorption of UV-A light. To potentiate this treatment, we have coated commercial glass plates with TiO2 nanoparticles prepared by the sol–gel method (TiO2-m), which exhibit a remarkable selectivity for the irreversible trapping of cancer cells. The physicochemical properties of the deposited TiO2-m nanoparticle coatings have been characterized by a number of complementary surface-analytical techniques and their interaction with leukemia and healthy blood cells were investigated. Scanning electron and atomic force microscopy verify the formation of a compact layer of TiO2-m nanoparticles. The particles are predominantly in the anatase phase and have hydroxyl-terminated surfaces as revealed by Raman, X-ray photoelectron, and infrared spectroscopy, as well as X-ray diffraction. We find that lymphoblastic leukemia cells adhere to the TiO2-m coating and undergo amoeboid-like migration, whereas lymphocytic cells show distinctly weaker interactions with the coating. This evidences the potential of this nanomaterial coating to selectively trap cancer cells and renders it a promising candidate for the development of future prototypes of PDT devices for the treatment of leukemia and other types of cancers with non-adherent cells.

New isoreticular phosphonate MOFs based on a tetratopic linker - Steinke, Felix; Javed, Ali; Wöhlbrandt, Stephan; Tiemann, Michael; Stock, Norbert (Dalton Transactions)
The tetratopic linker 1,1,2,2-tetrakis(4-phosphonophenyl)ethylene (H8TPPE) was used to synthesize the three new porous metal–organic frameworks of composition [M2(H2O)2(H2TPPE)]·xH2O (M = Al3+, Ga3+, Fe3+), denoted as M-CAU-53 under hydrothermal reaction conditions, using the corresponding metal nitrates as starting materials. The crystal structures of the compounds were determined ab initio from powder X-ray diffraction data, revealing small structural differences. Proton conductivity measurements were carried out, indicating different conductivity mechanisms. The differences in proton conductivity could be linked to the individual structures. In addition, a thorough characterization via thermogravimetry, elemental analysis, IR-spectroscopy as well as N2- and H2O-sorption is given.

Etwas anarchischer, freier, ungewohnter (Ein Gespräch mit Birgit Eickelmann) - Eickelmann, Birgit (Chancen denken. Impulse für eine offene und mutige Gesellschaft im 21. Jahrhundert)

Ungleichheiten im Bildungssystem – eine unangenehme Konstante. Sinnvolle Maßnahmen und die Grenzen des Möglichen - Eickelmann, Birgit; Maaz, Kai (Schule weiter denken)

Wie Lernen in digitalen Lernumgebungen motivieren kann – Stichwort: Gamification - Bonanati, Sabrina; Buhl, Heike M.; Eickelmann, Birgit

External Focus of Attention Influences Cortical Activity Associated with Single Limb Balance Performance - Sherman, David A; Lehmann, Tim; Baumeister, Jochen; Gokeler, Alli; Donovan, Luke; Norte, Grant E (Physical Therapy)
Abstract Objective External focus (EF) of attention leads to improved balance performance. Consideration of the neuromodulatory effects of EF may inform its clinical utility in addressing neuroplastic impairments after musculoskeletal injuries. We aimed to determine whether electrocortical activity and balance performance changed with attentional foci that prioritized differing sensory feedback and whether changes in electrocortical activity and balance were associated. Methods Individuals who were healthy (n = 15) performed a single-limb balance task under 3 conditions: internal focus (IF), somatosensory focus [EF with a baton (EF-baton)], and visual focus [EF with a laser (EF-laser)]. Electrocortical activity and postural sway were recorded concurrently using electroencephalography and a triaxial force plate. Electroencephalographic signals were decomposed, localized, and clustered to generate power spectral density in θ and α-2 frequency bands. Postural sway signals were analyzed with center-of-pressure sway metrics (eg, area, distance, velocity) and knee angle. The relationship between percent change in clustered brain activity and task performance metrics was assessed. Results Both EF conditions resulted in increased cortical activity and improved balance performance compared to IF. EF-laser had the largest effect, demonstrating increased frontal θ power (d = 0.64), decreased central θ power (d = −0.30), and decreased bilateral motor, bilateral parietal, and occipital α-2 power (d = −1.38 to −4.27) as well as a shorter path distance (d = −0.94) and a deeper (d = 0.70) and less variable (d = −1.15) knee angle than IF. Weak to moderate associations exist between increases in cortical activity and improved balance performance (ρ = 0.405–0.584). Conclusions EF resulted in increased cortical activity associated with cognitive, motor, somatosensory, and visual processing. EF-laser, which prioritized visual feedback, had the largest and broadest effects. Changes in cortical activity resulting from EF were independently associated with improved balance performance. Impact This study demonstrates that goal-oriented attention results in functional increases in brain activity compared to internally directed self-focus. These results suggest EF may target neurophysiologic impairments and improve balance in clinical populations.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.
Keywords: Behavioral Neuroscience; Biological Psychiatry; Psychiatry and Mental health; Neurology; Neuropsychology and Physiological Psychology

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.
Keywords: General Neuroscience

EEG‑derived brain graphs are reliable measures for exploring exercise‑induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Keywords: Multidisciplinary

Theoretische Beschreibung des Tropfenbildungsprozesses bei der Filament Extension Atomization: Entwicklung eines Vorhersagemodells für die Tropfengröße (Poster) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Filament Extension Atomization – A novel Process for Powder Production? (Presentation) - Neukötter, Moritz; Jesinghausen, Steffen; Schmid, Hans-Joachim

Bewegungsförderung in Ganztagsschulen - Möhring, Julia; Krumhöfner, Anika; Gräfin von Plettenberg, Elisabeth Gudila Sophia Ida Maria (-)

Veranstaltungsbericht: Immaterielles Kulturerbe in Nordrhein-Westfalen – Steigerlied und Trinkhallenkultur im Ruhrgebiet erhalten Auszeichnung anlässlich der Neuaufnahmen in das nordrhein-westfälische Landesinventar - Leineweber, Jonas

Tagungsbericht: Immaterielles Kulturerbe und regionale Identität. Gesellschaftliche Repräsentation und Partizipation im Schützenwesen - Leineweber, Jonas

A Study about Schottky Barrier Height and Ideality Factor in Thin Film Transistors with Metal/Zinc Oxide Nanoparticles Structures Aiming Flexible Electronics Application - Kaufmann, Ivan Rodrigo; Zerey, Onur; Meyers, Thorsten; Reker, Julia; Vidor, Fábio; Hilleringmann, Ulrich (Nanomaterials)
Zinc oxide nanoparticles (ZnO NP) used for the channel region in inverted coplanar setup in Thin Film Transistors (TFT) were the focus of this study. The regions between the source electrode and the ZnO NP and the drain electrode were under investigation as they produce a Schottky barrier in metal-semiconductor interfaces. A more general Thermionic emission theory must be evaluated: one that considers both metal/semiconductor interfaces (MSM structures). Aluminum, gold, and nickel were used as metallization layers for source and drain electrodes. An organic-inorganic nanocomposite was used as a gate dielectric. The TFTs transfer and output characteristics curves were extracted, and a numerical computational program was used for fitting the data; hence information about Schottky Barrier Height (SBH) and ideality factors for each TFT could be estimated. The nickel metallization appears with the lowest SBH among the metals investigated. For this metal and for higher drain-to-source voltages, the SBH tended to converge to some value around 0.3 eV. The developed fitting method showed good fitting accuracy even when the metallization produced different SBH in each metal-semiconductor interface, as was the case for gold metallization. The Schottky effect is also present and was studied when the drain-to-source voltages and/or the gate voltage were increased.
Keywords: General Materials Science; General Chemical Engineering

Complementary Inverter Circuits on Flexible Substrates - Reker, Julia; Meyers, Thorsten; Vidor, Fabio F.; Joubert, Trudi-Heleen; Hilleringmann, Ulrich (2021 Smart Systems Integration (SSI))

Local Power Control using Wireless Sensor System for Microgrids in Africa - Hilleringmann, Ulrich; Petrov, Dmitry; Mwammenywa, Ibrahim; Kagarura, Geoffrey M. (2021 IEEE AFRICON)

The Viability of a Non-Flow Capacitive Biosensing Microsystem for Whole Cell Counting - Andrews, George; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (2021 IEEE AFRICON)

The Viability of a Non-Flow Capacitive Biosensing Microsystem for Whole Cell Counting - Andrews, George; Hilleringmann, Ulrich; Joubert, Trudi-Heleen (2021 IEEE AFRICON)

Die berufliche Tabletaneignung von Lehrkräften als Beispiel der Mediatisierung pädagogischer Handlungskontexte. Theoretische Perspektiven und empirische Befunde - Gerhardts, Lara; Dehmel, Lukas; Meister, Dorothee M. (Jahrbuch Medienpädagogik 16. Medienpädagogik in Zeiten einer tiefgreifenden Mediatisierung)

Zur Entgrenzung der Arbeit des medienpädagogischen Weiterbildungspersonals im Kontext tiefgreifender Mediatisierung - Dehmel, Lukas (Erwachsenenpädagogische Digitalisierungsforschung. Impulse - Befunde - Perspektiven. Bielefeld)

Epistemologies of predictive policing: Mathematical social science, social physics and machine learning - Hälterlein, Jens (Big Data & Society)

Spanning the isogeny class of a power of an elliptic curve - Kirschmer, Markus; Narbonne, Fabien; Ritzenthaler, Christophe; Robert, Damien (Mathematics of Computation)
Let E be an ordinary elliptic curve over a finite field and g be a positive integer. Under some technical assumptions, we give an algorithm to span the isomorphism classes of principally polarized abelian varieties in the isogeny class of E⁹ . The varieties are first described as hermitian lattices over (not necessarily maximal) quadratic orders and then geometrically in terms of their algebraic theta null point. We also show how to algebraically compute Siegel modular forms of even weight given as polynomials in the theta constants by a careful choice of an affine lift of the theta null point. We then use these results to give an algebraic computation of Serre’s obstruction for principally polarized abelian threefolds isogenous to E³ and of the Igusa modular form in dimension 4. We illustrate our algorithms with examples of curves with many rational points over finite fields.
Keywords: Applied Mathematics; Computational Mathematics; Algebra and Number Theory

Anette Baumann / Alexander Jendorff / Frank Theisen (Hgg.), Religion – Migration – Integration. Studien zu Wechselwirkungen religiös motivierter Mobilität im vormodernen Europa, Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Hendrik Meyer-Magister, Wehrdienst und Verweigerung als komplementäres Handeln. Individualisierungsprozesse im bundesdeutschen Protestantismus der 1950er Jahre (RBRD 7), Tübingen 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Jutta Stander-Dulisch, Glaubenskrisen, Neue Religionen und der Papst. Religion in „Stern“ und Spiegel“ von 1960 bis 2014, Bielefeld 2019 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Analytical Bound State Solutions of the Klein-Fock-Gordon Equation for the Sum of Hulthén and Yukawa Potential within SUSY Quantum Mechanics - Ahmadov, A. I.; Aslanova, S. M.; Orujova, M. Sh.; Badalov, S. V. (Advances in High Energy Physics)
The relativistic wave equations determine the dynamics of quantum fields in the context of quantum field theory. One of the conventional tools for dealing with the relativistic bound state problem is the Klein-Fock-Gordon equation. In this work, using a developed scheme, we present how to surmount the centrifugal part and solve the modified Klein-Fock-Gordon equation for the linear combination of Hulthén and Yukawa potentials. In particular, we show that the relativistic energy eigenvalues and corresponding radial wave functions are obtained from supersymmetric quantum mechanics by applying the shape invariance concept. Here, both scalar potential conditions, which are whether equal and nonequal to vector potential, are considered in the calculation. The energy levels and corresponding normalized eigenfunctions are represented as a recursion relation regarding the Jacobi polynomials for arbitrary l states. Beyond that, a closed form of the normalization constant of the wave functions is found. Furthermore, we state that the energy eigenvalues are quite sensitive with potential parameters for the quantum states. The nonrelativistic and relativistic results obtained within SUSY QM overlap entirely with the results obtained by ordinary quantum mechanics, and it displays that the mathematical implementation of SUSY quantum mechanics is quite perfect.
Keywords: Nuclear and High Energy Physics

Towards a Trust-Aware Item Recommendation System on a Graph Autoencoder with Attention Mechanism - Meydani, Elnaz; Düsing, Christoph; Trier, Matthias (Innovation Through Information Systems: Volume II: A Collection of Latest Research on Technology Issues)

Potassium titanyl phosphate Z- and Y-cut surfaces from density-functional theory - Neufeld, Sergej; Bocchini, Adriana; Schmidt, Wolf Gero (Physical Review Materials)

Surface localized phonon modes at the Si(553)-Au nanowire system - Plaickner, Julian; Speiser, Eugen; Braun, Christian; Schmidt, Wolf Gero; Esser, Norbert; Sanna, Simone (Physical Review B)

GaInP/AlInP(001) Interfaces from Density Functional Theory - Meier, Lukas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

InP and AlInP(001)(2 × 4) Surface Oxidation from Density Functional Theory - Ruiz Alvarado, Isaac Azahel; Karmo, Marsel; Runge, Erich; Schmidt, Wolf Gero (ACS Omega)

Lattice parameters and electronic band gap of orthorhombic potassium sodium niobate K0.5Na0.5NbO3 from density-functional theory - Bidaraguppe Ramesh, Nithin; Schmidt, Falko; Schindlmayr, Arno (The European Physical Journal B)
We perform a theoretical analysis of the structural and electronic properties of sodium potassium niobate K1-xNaxNbO3 in the orthorhombic room-temperature phase, based on density-functional theory in combination with the supercell approach. Our results for x=0 and x=0.5 are in very good agreement with experimental measurements and establish that the lattice parameters decrease linearly with increasing Na contents, disproving earlier theoretical studies based on the virtual-crystal approximation that claimed a highly nonlinear behavior with a significant structural distortion and volume reduction in K0.5Na0.5NbO3 compared to both end members of the solid solution. Furthermore, we find that the electronic band gap varies very little between x=0 and x=0.5, reflecting the small changes in the lattice parameters.

Erratum: Efficient implementation of the GW approximation within the all-electron FLAPW method [Phys. Rev. B 81, 125102 (2010)] - Friedrich, Christoph; Blügel, Stefan; Schindlmayr, Arno (Physical Review B)